Auditory Attention Is Divisible: Segregated Tone Streams Can Be Tracked Simultaneously. - Demany, Laurent; Erviti, Mayalen; Semal, Catherine (Journal of Experimental Psychology. Human Perception & Performance, 2015)
Can auditory attention be split? We addressed this question using rapid sequences of tones alternating in frequency between 2 remote registers. In these rapid sequences, consecutive tones could not be perceptually linked; the tones were instead inevitably segregated into 2 concurrent melodic streams. Listeners had to determine if the 2 melodies interleaved in a sequence were exact transpositions of each other or not. This task could be performed successfully. More crucially, performance was better when each component tone of 1 melody was immediately transposed in the other melody than when component i of 1 melody was a transposition of component i-1 of the other melody. Nevertheless, because the melodies were segregated, listeners were unable to determine which was the leading melody when 2 interleaved melodies were immediate transpositions of each other. Our results are inconsistent with the hypothesis that listeners compared concurrent melodic streams using a memory-based serial-processing strategy. It instead appears that listeners were able to track such streams in parallel. Therefore, attention can be split between concurrent sensory streams even when the physical entities making up these streams do not overlap in time.